2019
DOI: 10.3389/fvets.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Opinions of Third Year Veterinary Students Relevant to Animal Welfare Before and After Implementation of a Core Welfare Course

Abstract: Although leading veterinary organizations emphasize the importance of animal welfare knowledge, there exists a gap in current veterinary student animal welfare education and training. A survey instrument was created to assess third-year Doctor of Veterinary Medicine (DVM) student knowledge of key animal welfare topics, opinions regarding the inclusion of welfare education in the veterinary curriculum, and views on veterinarian responsibilities as advocates. In Spring 2018, Colorado State University added a req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…While perceptions of animal welfare have been assessed in different groups including veterinary students ( Abood and Seigford, 2012 ; Johnstone et al, 2019 ; Proudfoot and Ventura, 2021 ) and students internationally ( Freire et al, 2017 ; Mota-Rojas et al, 2018 ; Vargas-Bello-Pérez et al, 2021 ), there is still a lack of research regarding undergraduate and graduate animal science student perspectives of animal welfare as part of their education in the United States. Although there has been growth in the number of faculty members at universities specifically trained in animal welfare science ( Broom, 2005 ), the field is still novel and expanding relative to other more traditional animal science specialty areas, for example, nutrition, genetics, and meat science.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While perceptions of animal welfare have been assessed in different groups including veterinary students ( Abood and Seigford, 2012 ; Johnstone et al, 2019 ; Proudfoot and Ventura, 2021 ) and students internationally ( Freire et al, 2017 ; Mota-Rojas et al, 2018 ; Vargas-Bello-Pérez et al, 2021 ), there is still a lack of research regarding undergraduate and graduate animal science student perspectives of animal welfare as part of their education in the United States. Although there has been growth in the number of faculty members at universities specifically trained in animal welfare science ( Broom, 2005 ), the field is still novel and expanding relative to other more traditional animal science specialty areas, for example, nutrition, genetics, and meat science.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while courses in animal welfare seemed widely offered at the participating universities, the majority of survey respondents had not taken an animal welfare course previously. Several studies assessing veterinary student perspectives about the value of an animal welfare course before and after enrollment have shown generally positive responses, indicating improved confidence in researching and assessing welfare scenarios, increased agreement that an animal welfare course is a valuable component of the curriculum, and improved ability to identify and discuss ethical dilemmas ( Lord and Walker, 2009 ; Abood and Seigford, 2012 ; Johnstone et al, 2019 ). This survey did not ask students why they had or had not taken a welfare course, though this would be valuable information to request in future surveys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recommended in 1964 that disaster medical training be given during the veterinary curriculum due to potential difficulty in reaching post-graduate veterinarians stemming from disinterest and competing commitments (10). However, contemporary veterinary students have reported that the current curriculum is already heavy and allows little room for additional requirements; there would likely be little support for inclusion of human-specific disaster medicine (23,24). Fortunately, the elevated importance of animals in disaster preparation and planning following Hurricane Katrina with the Pet Evacuation and Transportation Standards (PETS) Act and Post-Katrina Emergency Management Reform Act has increased post-graduate veterinarian involvement in disaster management activities.…”
Section: Recommendations For Trainingmentioning
confidence: 99%